Determinasi Persepsi Etis Mahasiswa Akuntansi: Peran Gender, Hedonisme, Love of Money dan Machiavellian - Nila Hidayah; Muhammad Hendri Kurniawan; Asri Dwi Ariyani; Meutia Layli (IJMA (Indonesian Journal of Management and Accounting), 2026)
ABSTRACT The purpose of this study is to examine accounting students perceptions of ethical considerations related to gender, hedonism, love of money, and machiavellianism, where machiavellianism is a new variable added to this study because there are many cases of misconduct committed by accountants, which confirm the characteristics of this variable. Accounting students, as future accountants, were selected as respondents in order to gain a clear understanding of the duties and professionalism that must be maintained. This is because student behavior will influence their future behavior in the workplace. This study used a quantitative approach with primary data and descriptive statistical methods. Data analysis was performed using multiple linear regression techniques to test the extent to which the four independent variables collectively or individually influence the dependent variable. The results show that gender has no effect (Sig. 0,19 > 0.05) on students' ethical perceptions, while the variables of hedonism (Sig. 0,00 < 0.05) and love of money (Sig. 0,00 < 0.05), and machiavellianism (Sig. 0,00 < 0.05) did influence students' ethical perceptions. The implications of this study confirm that internal factors such as value orientation and personality traits have a greater influence on ethical perceptions than gender factors. Therefore, accounting education needs to emphasize the development of integrity and control of materialistic orientation in order to prevent potential professional misconduct in the future.   ABSTRAK Tujuan dari penelitian ini adalah untuk menguji persepsi mahasiswa akuntansi mengenai pertimbangan etis terkait variabel gender, hedonisme, love of money dan machiavellian, di mana machiavellian merupakan variabel baru yang ditambahkan dalam penelitian ini sebab ada banyak kasus penyimpangan yang dilakukan para akuntan, yang menegaskan karakteristik dari variabel tersebut. Mahasiswa akuntansi sebagai calon akuntan dijadikan responden dengan tujuan agar dapat memahami dengan jelas dan mengetahui apa saja tugas dan profesionalitas yang harus dijaga. Sebab perilaku mahasiswa akan mempengaruhi bagaimana perilaku mereka nantinya di dunia kerja. Penelitian ini menggunakan pendekatan kuantitatif data primer dengan metode statistik deskriptif. Analisis data dilakukan dengan teknik regresi linier berganda untuk menguji sejauh mana ke empat variabel independen secara bersama-sama atau individual mempengaruhi variabel dependen. Hasil menunjukkan gender tidak berpengaruh (Sig. 0,19 > 0,05) terhadap persepsi etis mahasiswa, sementara variabel hedonisme (Sig. 0,00 < 0,05), love of money (Sig. 0,00 < 0,05) dan machiavellian (Sig. 0,00 < 0,05) berpengaruh terhadap persepsi etis mahasiswa. Implikasi dari penelitian ini menegaskan bahwa faktor internal berupa orientasi nilai dan karakter kepribadian lebih menentukan persepsi etis dibanding faktor gender. Maka, pendidikan akuntansi perlu menekankan pembentukan integritas dan pengendalian orientasi materialistik guna mencegah potensi penyimpangan profesi di masa depan.